Analysis of Growth of Fdi In India: Exploring FDI Growth in India and its Economic Implications (Journal of Advances and Scholarly Researches in Allied Education, 2012)
Considering the large number of motives an individualfirm can have to undertake FDI; it is not surprising that there exists nogeneral theory that can comprehensively explain the existence of MNCs and FDI.As a result of this, the FDI literature is diverse and spans over severaldifferent disciplines including international economics, economic geography,international business as well as management. There exist several studiesproviding overviews of FDI theories, for example, Agarwal , Cantwell ,Meyer  and Markusen . Whereas this paperprimarily focuses on a developing economy, most of the theories described inthis section can be applied to all types of economies.